2021
DOI: 10.3390/pharmaceutics13010116
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Peptide Dendrimers for Delivery of Splice-Switching Oligonucleotides

Abstract: Non-viral transfection reagents are continuously being developed in attempt to replace viral vectors. Among those non-viral vectors, dendrimers have gained increasing interest due to their unique molecular structure and multivalency. However, more improvements are still needed to achieve higher efficacy and lower toxicity. In this study, we have examined 18 peptide dendrimers conjugated to lipophilic moieties, such as fatty acids or hydrophobic amino acids, that were previously explored for siRNA. Reporter cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Dendrimer systems can also incorporate lipid or polymers to obtain greater efficacy. It has been demonstrated that transfection was enhanced by the addition of a polyol to the lipid/dendrimer hybrid ( 49 ) or a polymer excipient, such as Polyvinylalcohol 18 (PVA 18) ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dendrimer systems can also incorporate lipid or polymers to obtain greater efficacy. It has been demonstrated that transfection was enhanced by the addition of a polyol to the lipid/dendrimer hybrid ( 49 ) or a polymer excipient, such as Polyvinylalcohol 18 (PVA 18) ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, peptide dendrimers with covalently attached lipophilic tails showed efficient transfection without lipofectin. 6,7,11,12 Two very efficient third-generation peptide dendrimer sequences, MH18 and MH13 (Figure 1A,B), 10,11 are constituted by leucines and lysines, with a tetra-leucine or two palmitoyl groups as a hydrophobic core, respectively. By changing the chirality of these sequences and performing a few mutations in the sequences, it was possible to modulate the affinity for nucleic acids and their performances as transfecting agents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chemical modification, a more generic approach to improve TNA performance involves the use of cationic and/or lipophilic transfection reagents, which increase cell membrane penetration and cytosolic accumulation of oligonucleotides. [ 30–32 ] Furthermore, functionalized nanocarriers, modified with, for example, targeting agents and cell penetrating enhancers could increase their intracellular delivery and efficacy, thereby reducing dosages and potential immunogenicity. [ 33–37 ]…”
Section: Introductionmentioning
confidence: 99%